Profiling Isokinetic Strength of Shoulder Rotator Muscles in Adolescent Asymptomatic Male Volleyball Players - Claudio Andre Barbosa de Lira; Valentine Zimermann Vargas; Rodrigo Luiz Vancini; Marilia Santos Andrade (MDPI AG, 2019)
The aim of the study was to describe the strength symmetry of internal and external rotator muscles and the conventional and functional strength balance ratios between these muscles in adolescent male volleyball players. Twenty-eight male adolescent volleyball players (15.5 ± 1.1 years (15⁻17 years); 73.2 ± 10.9 kg (55.3⁻100.1 kg) and 184.9 ± 8.4 cm (170⁻209 cm)) participated in this cross-sectional study. Concentric and eccentric peak torque of external and internal rotator muscles were measured, and conventional and functional strength balance ratios were calculated. The dominant limb presented significantly higher values for peak torque than the non-dominant limb of internal rotator muscles at concentric action assessed at 60°/s (48.7 ± 13.7 Nm and 43.9 ± 11.6 Nm, p = 0.01 and d value = 0.37) and at 240°/s (44.7 ± 11.2 Nm and 41.1 ± 11.0 Nm, p = 0.03 and d = 0.32). However, there was no difference in the peak torque of external rotator muscle between limbs for either angular speed. Regarding strength balance ratios, neither conventional (74.8 ± 14.3 for dominant limb and 80.1 ± 14.0 for non-dominant limb, p = 0.06 and d = 0.37) nor functional ratio (1.2 ± 0.4 for dominant limb and 1.3 ± 0.5 for non-dominant limb, p = 0.06 and d = 0.22) presented significant contralateral differences. Despite the short practice time, adolescent male volleyball athletes already have significant contralateral differences for internal rotator muscles and conventional ratio tends to be asymmetrical. Thus, preventive shoulder-strengthening programs, focused on the internal rotator muscles of the non-dominant limb, aiming to correct contralateral deficiency and conventional ratio, may be warranted for this population in the process of biological growth, maturation and development.